Etika Keluarga dalam Kearifan Digital - Indriyanti, Indriyanti; Sennahati, Sennahati; Mattarima, Mattarima; Hukmah, Anil (Departement of Communication Sciences, Faculty of Social and Political Sciences, UIM, 2023)
Technology causes many changes both in society and in the family. The most common change in families is the change in communication behavior. Due to the busyness of each family, they rely on family chat applications to provide information between them. Therefore, the purpose of this research is to find out 1) How does the family communicate in the family group when chatting? 2) Is there an ethical impact felt by the family by chatting through the application?This research uses a qualitative method with a phenomenological approach and the theory used is phenomenological theory. The results of this study are 1. Chats conducted by families through the application do not experience obstacles in conveying messages. In general, they feel happy because the purpose of their message can be conveyed even without having to meet face to face. 2.Ethics in the family unwittingly become eroded due to the lack of face-to-face communication. The humanity of the family slowly diminishes due to the lack of nonverbal communication such as gaze, caress, touch, hug, or kiss between parents and children.